An Overview of Bidirectional AC-DC Grid Connected Converter Topologies for Low Voltage Battery Integration - Kaspars Kroics; Oleksandr Husev; Kostiantyn Tytelmaier; Janis Zakis; Oleksandr Veligorskyi (Institute of Advanced Engineering and Science, 2018)
Battery energy storage systems are becoming more and more popular solution in the household applications, especially, in combination with renewable energy sources. The bidirectional AC-DC power electronic converter have great impact to the overall efficiency, size, mass and reliability of the storage system. This paper reviews the literature that deals with high efficiency converter technologies for connecting low voltage battery energy storage to an AC distribution grid. Due to low voltage of the battery isolated bidirectional AC-DC converter or a dedicated topology of the non isolated converter is required. Review on single stage, two stage power converters and integrated solutions are done in the paper.